Retail career attractiveness to college students: Connecting individual characteristics to the trade-off of job attributes. (July 2016) - Oh, Hyunjoo; Weitz, Barton; Lim, Jeremy
Abstract: This study examines how U.S. business college students evaluate the attractiveness of potential job opportunities by making trade-offs among important job attributes. Using a conjoint approach, we examine the relative importance of industry type, starting salary, five-year salary, training, benefits, and work-life balance in job choice decisions. We also examine the effects of job applicants' career expectations and core competencies on their job choice determinants. An analysis of 162 business students' evaluations of 27 job profiles indicates that five-year-salary outweighs all other attributes. Their career expectations and core competencies have a substantial influence on their ensuing job choice. We suggest recruitment strategies to target recent college graduates with consideration of individuals' different career expectations and core competencies.